The secret of the Fortune Wookiee - Angleberger, Tom (Angleberger, Tom. Origami Yoda book, 2012)
McQuarrie Middle School's students miss Origami Yoda when Dwight leaves for Tippett Academy, but he sends Sara a paper Fortune Wookiee that seems to give advice just as good as Yoda's--even if, in the hands of girls, it seems preoccupied with romance.